Pembinaan Karakter Mahasiswa di Ma’had UIN Ar-Raniry Banda Aceh - Putri Munita; Anton Widyanto (Tadabbur: Jurnal Peradaban Islam, 2021)
One of the functions of education is to form the character of students. Character building is a system of inculcating character values ​​to students through competency achievement activities in accordance with the level of education. Character education at the institutional level leads to the formation of values ​​that underlie individual behavior applied in society. The problem that arises in this research lies in fostering student character so that it gives rise to several research questions such as: How to plan students’ character development at Ma'had UIN Ar-Raniry Banda Aceh in building student character, How is the implementation of the Ma'had UIN Ar-Raniry Banda Aceh program in fostering student character and what are the implications of the Ma'had UIN Ar-Raniry Banda Aceh program in fostering students’ character. The purpose of this study is to determine the efforts made by ustaz ustazah in planning student character development in Ma'had, to determine the implementation of the Ma'had UIN Ar-Raniry Banda Aceh program and to find out what are the implications of the Ma'had UIN Ar-Raniry Banda Aceh program. in building student character. The research method in this thesis uses qualitative research methods in the form of descriptive analysis. Data collection was carried out using observation, interview and documentation techniques. The results in this thesis research indicate that planning at the beginning of the program that students are required to live in a dormitory and the role of dorm supervisor is very important for students in the dormitory. They carry out disciplinary attitudes through congregational prayers, Implementation of the Ma'had program through the Tsaqafah Islamiyah program, the Tahsin program and the Dormitory program. The ma'had program is very beneficial for students, because undergoing activities in a dormitory is like living in an Islamic boarding school. Surely, it really helps them in doing good things, especially in worship to get closer to the Khaliq and many other positive things that students get during this program. They can manage their time in discipline.